2019
DOI: 10.1002/chem.201903824
|View full text |Cite
|
Sign up to set email alerts
|

Unusual η1‐Coordinated Alkyne and Alkene Complexes

Abstract: This mechanistic study demonstrates that an unusual h 1 -coordinated alkyne complex is criticalf or the 1-pentyne 1,1-diboration reaction. The comparatives tudies suggest the "pull-push" antagonistic effect arising from Lewis acidity and steric congestion as the reason for the existence of h 1 -coordinated alkyne complexes. Analogous h 1 -coordinated alkene complexes are also predicted and seem to be promising for their applicationt ot he important olefin polymerization reaction.Scheme1.Synthesis of 1,1-and 1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Finally, the CC hydrogenation product C6a is achieved, and the α-methylation of propiophenone is completed. It should also be noted that no coordination of CC bond to the metal atom is involved for the enone CC hydrogenation in this study, although the Dewar–Chatt–Duncanson η 2 -coordination model is generally reported in the previous studies on the CC activations in alkene hydrogenations. Actually, in the whole reaction, the carbonyl ligand serves as a catalytic center.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the CC hydrogenation product C6a is achieved, and the α-methylation of propiophenone is completed. It should also be noted that no coordination of CC bond to the metal atom is involved for the enone CC hydrogenation in this study, although the Dewar–Chatt–Duncanson η 2 -coordination model is generally reported in the previous studies on the CC activations in alkene hydrogenations. Actually, in the whole reaction, the carbonyl ligand serves as a catalytic center.…”
Section: Results and Discussionmentioning
confidence: 99%
“…In accordance with our previous theoretical studies on homogeneous hydrogenation and dehydrogenation reactions, we adopted the DFT ωB97X-D method in this study using the Gaussian 09 program . Geometries were optimized in a methanol solution using the BS-I basis sets, where the 6-311G­(d,p) basis sets were used for nonmetal atoms, and the SDD basis sets with effective core potentials were used for the Mn, Cs, and Ru atoms. The single-point energy refinements were further performed with the BS-II basis sets, where the def2-TZVPP basis sets were used for all atoms. , Thermal corrections and entropy contribution to the Gibbs free energy were obtained with the ωB97X-D/BS-I methods.…”
Section: Methodsmentioning
confidence: 99%
“…In accordance with previous computational studies on borylation reactions catalyzed by transition-metal complexes, all calculations were carried out by the DFT method with the ωB97X-D method using the Gaussian 09 program . In the geometry optimization, the SDD basis set is used for the Ir center and 6-311G­(d,p) , basis sets are used for all of the other atoms .…”
Section: Methodsmentioning
confidence: 99%
“…DIA shows that the difference in total distortion energy between TSC4–5 E and TSC4–5 Z is small (16.83 vs 16.82 kcal/mol), and the lower energy of TSC4–5 E compared with TSC4–5 Z is mainly caused by the stronger interaction between the metal complex and monomer moiety (−36.89 vs −33.95 kcal/mol). The interaction between the organometallic complex and unsaturated hydrocarbons could be described by the Dewer–Chatt–Duncanson model. The metal–ligand interaction could be considered to arise from the electron pair delocalization, in which a donation of olefin π-electrons into the metal and back-donation from the metal into the olefin π* orbital occur. Meanwhile, the natural bond orbital (NBO) analysis shows the acceptor–donor interactions between the Pd–H bond and C1C2 bond.…”
Section: Computational Studiesmentioning
confidence: 99%